Marketing tools to support university library’s mission - Trtíková, Ilona; Němečková, Lenka (ISAST, 2012)
This paper is focused on the use of marketing tools in academic libraries based on an example of the Central Library (CL) of the Czech Technical University in Prague (CTU). An initial important marketing tool is the segmentation of the CL users into specific target groups and specification of their individual needs and requirements. The CL serves its students and academic staff, supports the development of their information literacy skills and assists to form their key competencies for their lifelong education, future profession and career. Marketing tools can be well used to support the evaluation of R&D activities. Besides this CL also helps to promote and increase the prestige of the university and its academic community as a whole. The paper describes a broad range of marketing activities including electronic tools and services that help the library to meet its goals.
Keywords: academic library; marketing tools; marketing mix; library services; information resources; R&D support; study support; value-added tools